STUDI FENOMENOLOGI EKSPLORASI MODEL PENGAMBILAN KEPUTUSAN KONSUMEN ANAK PADA KONSUMSI JAJANAN SEKOLAH - Anna Triwijayati (Manajemen dan Bisnis, 2013)
Children consumers are a potential segment because they have pocket money and do the buying behavior. Consuming snacks at school is typical children behavior in Indonesia. Research on how children make decision of their consumption is very interesting and useful because there has never been a similar study thoroughly examined the specific decision making of children consumers. This study aims to construct a theory of decision making of buying snacks by children consumers. The research method used is phenomenology. Phenomenology method is utilized in order to get meaningful and ‘live’ children’s experiences. Based on the stages of data collection, analysis and classification of the themes, this result obtained 22 themes related to children consumer decision making. All of themes are processed into meaning essential and from this gives propotitions and model of children consumer decision making.The result shows that children consumer decision making process is determined by these factors: internal children their self, teacher’s references, parents, conditioning and snack product. The process have three stages which are driving physical and psychological need factors, process of quick alternative evaluation of snack products, and unplanned decision.